Ferulated Poly(vinyl alcohol) based hydrogels - Simone Pepi; Marco Paolino; Mario Saletti; Jacopo Venditti; Luigi Talarico; Marco Andreassi; Germano Giuliani; Gianfranco Caselli; Roberto Artusi; Andrea Cappelli; Gemma Leone; Agnese Magnani; et al. (Heliyon, 2023)
New graft copolymers were prepared by reaction of poly (vinyl alcohol) (PVA) with mono-imidazolide or bis-imidazolide derivatives of ferulic acid (FA) with the formation of ester bonds. The obtained graft copolymers, thanks to the crosslinking capability of FA, formed in water strong gels as verified by rheological analyses. The resulting hydrogels were characterized to evaluate their applicability as wound dressing. In this perspective, their capability to absorb and retain a large amount of fluid without dissolving was verified by swelling kinetics and Moisture Vapour Transmission Rate measurements. Their stability towards mechanical solicitations was assessed by quantifying elasticity, compliance, stress-relaxation, and adhesivity properties. The analyses pointed out that hydrogel PVA-FA2-3 obtained by feruloylation of PVA with bis-imidazole derivative of ferulic acid using an acylation agent/polymer molar ratio 0.03/1 resulted the best candidate for the foreseen application.